2010
DOI: 10.1177/0003319710380680
|View full text |Cite
|
Sign up to set email alerts
|

Great Saphenous Vein Radiofrequency Ablation Versus Standard Stripping in the Management of Primary Varicose Veins-A Randomized Clinical Trial

Abstract: Great saphenous vein occlusion was achieved efficiently in 94% of our group using RFA with minimal complications and obvious advantages as compared to standard surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
1
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 22 publications
3
50
1
10
Order By: Relevance
“…37,38 After 24 months, the success rate was 85.2%-95.8%. 26,36 Proebstle and colleagues 31 reported a success rate of 92.6% at 36 months, and Pisano and colleagues 37 indicated a success rate of 100% for follow-up of up to 5 years. In these last 2 studies, the attrition rate at 36 months and 60 months was, however, not provided.…”
Section: Efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…37,38 After 24 months, the success rate was 85.2%-95.8%. 26,36 Proebstle and colleagues 31 reported a success rate of 92.6% at 36 months, and Pisano and colleagues 37 indicated a success rate of 100% for follow-up of up to 5 years. In these last 2 studies, the attrition rate at 36 months and 60 months was, however, not provided.…”
Section: Efficacymentioning
confidence: 99%
“…Across all studies, the occlusion rates at less than 3 months were usually 93%-100%, 11,13,15,25,31,36,37,41 with a weighted average of 98% (weighting was performed according to the number of legs treated in each study). The venous occlusion rate at 6 months was reported as being close to 90% in 4 studies included in the MAS review 20 but appeared to be higher in more recent studies, 98.6%-100%, 8,26,28,35 for a weighted average of 98.8%.…”
Section: Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…62,72,73 Multiple RCTs consistently demonstrated that modern open surgery, radio frequency and laser ablation were equivalent in both effectiveness and safety in saphenous vein intervention. [74][75][76][77][78] Moreover, foam sclerotherapy was shown to be an effective saphenous ablative procedure but had a significantly higher recanalization rate on the treated saphenous segments compared to other ablative or surgical methods. 79 Perforator venous reflux demonstrated its role in VLU formation based on the literature.…”
Section: Endovascular and Surgical Managementmentioning
confidence: 99%
“…[1,2] Compared to these invasive surgical interventions, modern endovenous techniques, such as endovenous laser therapy, radiofrequency ablation, and endovenous foam sclerotherapy, are more effective and associated with lower complication rates. [1][2][3][4] Nevertheless, while performing these endovenous techniques, patients still experience pain for which effective anesthesia is needed. Endovenous procedures are performed in the outpatient setting, and patients are discharged on the same day of the procedure; therefore, the method of anesthesia must also be suitable for the outpatient protocols.…”
mentioning
confidence: 99%